Characterization of metabolic features derived from the non-polar metabolite UHPLC-QTOF dataset of Jaspis sp. Collected from the waters off Pulau Banggi, Sabah, MalaysiaMendeley Data - Dexter Jiunn Herng Lee; Yee-Soon Ling; Christopher Lok Yung Voo; Mok Sam Lum; Jualang Azlan Gansau (Data in Brief)
The marine biome is a rich source of bioactive compounds. The discovery of anti-cancer compounds in Cryptotheca crypta in 1950 initiated a wave of bioprospecting efforts focused on marine sponges. Jaspis sp., a marine sponge, has been reported to exhibit anti-cancer activity against human colorectal cancer. A sample of Jaspis sp., collected from the waters off Pulau Banggi, Sabah, Malaysia, was analyzed through a non-polar metabolite survey. The non-polar crude extract was profiled using UHPLC-QTOF in both positive and negative modes. The detected metabolic features were clustered, and representative features were tentatively identified through a combination of spectral database searches (using various MS2 spectral databases) and in silico compound identification. This dataset provides a valuable foundation for future bioprospecting endeavors involving Jaspis sp.